2015
DOI: 10.1002/hed.24220
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baseline patient‐reported dysphagia on acute gastrostomy placement in patients with head and neck squamous cell carcinoma undergoing definitive radiation

Abstract: Baseline dysphagia-related symptoms before radiation are independent predictors of gastrostomy placement. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1318-E1324, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Traditionally requirement for gastrostomy in patients with HNSCC has been associated with dysphagia (Lango et al, 2016) or odynophagia from mucositis (Trotti et al, 2003), as these symptoms present as the physical inability to eat or drink. A review of the influence of nutrition impact symptoms on nutritional status, weight loss, and oral intake found most studies report on dysphagia and xerostomia (Bressan et al, 2016), with loss of appetite shown to have the greatest reduction on oral intake (Farhangfar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Traditionally requirement for gastrostomy in patients with HNSCC has been associated with dysphagia (Lango et al, 2016) or odynophagia from mucositis (Trotti et al, 2003), as these symptoms present as the physical inability to eat or drink. A review of the influence of nutrition impact symptoms on nutritional status, weight loss, and oral intake found most studies report on dysphagia and xerostomia (Bressan et al, 2016), with loss of appetite shown to have the greatest reduction on oral intake (Farhangfar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The highest level of evidence identifies: tumours of the oropharynx (Barnhart et al, 2017), followed by the hypopharynx and oral cavity (Ottosson et al, 2013); higher T stage (Brown et al, 2016a); higher overall TNM stage (Lango et al, 2016;Ottosson et al, 2013); and chemotherapy (Barnhart et al, 2017;Brown et al, 2016a;Lango et al, 2016). All of these factors were supported by a large number of level III-IV studies as well.…”
Section: Predictors Of Tube Feedingmentioning
confidence: 97%
See 3 more Smart Citations